1991
DOI: 10.1128/jb.173.15.4851-4861.1991
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis and characterization of the Escherichia coli hya operon, which encodes [NiFe] hydrogenase 1

Abstract: Deletion mutants of Escherichia coli specific for hydrogenase isoenzyme 1 (HYD1) have been constructed and characterized. The hya operon, which contains genes for the two HYD1 structural subunits and four additional genes, was mapped at 22 min on the E. coli chromosome. The total hydrogenase activities of the HYD1-negative mutant and wild-type strains were similar. However, the formate dehydrogenase activity associated with the formate hydrogen lyase pathway was lower in the mutant. The hya mutant (strain AP1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
99
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 37 publications
5
99
0
Order By: Relevance
“…The AltDE HupH protein also shares 10 % identity with HyaF from E. coli. Interestingly, in a case similar to our findings in this study, an E. coli hyaF mutant produced a functional hydrogenase in the absence of hyaF, but activity increased when this gene was reintroduced (Menon et al, 1991). HupH and HoxQ from Rhizobium leguminosarum and Ralstonia eutropha, respectively, were found to be essential for expression of an active hydrogenase and it was suggested that they may be involved in proper maturation of the hydrogenase small subunit (Bernhard et al, 1996;Manyani et al, 2005).…”
Section: Discussionsupporting
confidence: 73%
“…The AltDE HupH protein also shares 10 % identity with HyaF from E. coli. Interestingly, in a case similar to our findings in this study, an E. coli hyaF mutant produced a functional hydrogenase in the absence of hyaF, but activity increased when this gene was reintroduced (Menon et al, 1991). HupH and HoxQ from Rhizobium leguminosarum and Ralstonia eutropha, respectively, were found to be essential for expression of an active hydrogenase and it was suggested that they may be involved in proper maturation of the hydrogenase small subunit (Bernhard et al, 1996;Manyani et al, 2005).…”
Section: Discussionsupporting
confidence: 73%
“…It is still unknown in which oT der these processes take place and whether further reactions a e required. It has been shown that nickel insertion into the p:ecursors is a prerequisite for the large subunit C-terminal p~ ocessing of the hydrogenase of A. vinelandii [23], HYD1 [24] a~Ld HYD3 of E. coli [25]. In this communication, we show tlat the intracellular availability of nickel is essential for I-i YD2 translocation to the periplasmic side of the membrane.…”
Section: Discussionmentioning
confidence: 62%
“…Here we found that some genes encoding enzymes for energy metabolism under acid-and/or anaerobic conditions were under the direct control of BasSR (see Tables 1 and 2): (1) both aceF and aceE are members of the pyruvate dehydrogenase operon, which is involved in acetate metabolism (Quail et al, 1994); (2) the hyaA and hyaB genes encode the small and large subunits of hydrogenase 1, respectively (Menon et al, 1991); and (3) the cydAB operon encodes cytochrome bd-I terminal oxidase (Green et al, 1984), which is expressed under oxygen-limited conditions and needed for growth under anaerobic conditions (Cotter et al, 1990). The expression levels of these genes were increased under acidic and/or anaerobic growth conditions.…”
Section: Regulation Targets Of Bassr: Group 2 Genes For Modification mentioning
confidence: 99%